Current Issues of Career Choice for Debrecen Vocational School Students - Kőmíves, Péter Miklós; Erdős, A.; Körösparti, Péter (International Journal of Engineering and Management Sciences, 2018)
The aim of the article is to share information about the learning characteristics of the Z-generation based on literature review. In the same way based on secondary research we are showing the characteristics of the lifelong learning processes with special regards to the informal and non formal learning processes. On other hand we are publishing the outcomes of our research based on a survey done in three secondary schools of Debrecen. In the survey we investigated the learning plans of the vocational program students studying in the three secondary schools and their labour market perspectives.